2008
DOI: 10.1007/s10339-008-0219-x
|View full text |Cite
|
Sign up to set email alerts
|

Automatic quantity processing in 5-year olds and adults

Abstract: In this study adults performed numerical and physical size judgments on a symbolic (Arabic numerals) and non-symbolic (groups of dots) size congruity task. The outcomes would reveal whether a size congruity effect (SCE) can be obtained irrespective of notation. Subsequently, 5-year-old children performed a physical size judgment on both tasks. The outcomes will give a better insight in the ability of 5-year-olds to automatically process symbolic and non-symbolic numerosities. Adult performance on the symbolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
76
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 47 publications
12
76
9
1
Order By: Relevance
“…In fact, it would require a Weber fraction greater than infinity to successfully model individuals' who score less than 0.5. While such a score would appear impossible if the nonsymbolic comparison task involves only Weber-Fechner processes (a claim which is disputed by some researchers), some participants do indeed perform in this range: 10 of the 420 experimental quarters in our study resulted in accuracies below 0.5, and in Libertus et al's (2011) Fuhs & McNeil, 2013;Gebuis, Cohen Kadosh, de Haan, & Henik, 2009;Gilmore et al, 2013;Hurewitz, Gelman & Schnitzer, 2006;Nys & Content, 2012) and others have proposed alternative accounts entirely (e.g. Gebuis & Reynvoet, 2011bVerguts & Fias, 2004;Zorzi & Butterworth, 1999).…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…In fact, it would require a Weber fraction greater than infinity to successfully model individuals' who score less than 0.5. While such a score would appear impossible if the nonsymbolic comparison task involves only Weber-Fechner processes (a claim which is disputed by some researchers), some participants do indeed perform in this range: 10 of the 420 experimental quarters in our study resulted in accuracies below 0.5, and in Libertus et al's (2011) Fuhs & McNeil, 2013;Gebuis, Cohen Kadosh, de Haan, & Henik, 2009;Gilmore et al, 2013;Hurewitz, Gelman & Schnitzer, 2006;Nys & Content, 2012) and others have proposed alternative accounts entirely (e.g. Gebuis & Reynvoet, 2011bVerguts & Fias, 2004;Zorzi & Butterworth, 1999).…”
Section: Discussioncontrasting
confidence: 50%
“…Furthermore, it may be that the lack of the predicted relationship between NRE(accuracy) and Weber fraction has some theoretical significance, implying that there are important processes involved in the nonsymbolic comparison task which do not follow the Weber-Fechner law (as suggested by, for example, Fuhs & McNeil, 2013;Gebuis, Cohen Kadosh, de Haan, & Henik, 2009;Gebuis & Reynvoet, 2011bGilmore et al, 2013;Hurewitz, Gelman & Schnitzer, 2006;Nys & Content, 2012;Verguts & Fias, 2004;Zorzi & Butterworth, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the task, children were shown the digits 2 and 5 congruently with regard to their physical and numerical magnitude (5 2) as well as incongruently with regard to their physical and numerical magnitude (5 2). In contrast to previous studies involving speeded responses (Bugden & Ansari, 2011;Gebuis, Kadosh, de Haan, & Henik, 2009;Girelli, Lucangeli, & Butterworth, 2000;Rubinsten, Henik, Berger, & Shahar-Shalev, 2002) children in our study responded on their own accord. Of interest was whether they would be incorrect more often in incongruent trials and point towards the physically rather than the numerically larger digit, as compared to congruent trials.…”
contrasting
confidence: 54%
“…Indeed, a large number of studies have shown that numerical judgments are highly influenced by the visual perceptual properties of the stimulus (e.g. density, sum of perimeter, surface area, length, size…) in children and adults (Dormal & Pesenti, 2007;Gebuis, Cohen Kadosh, de Haan, & Henik, 2009;Rousselle & Noël, 2008;Rousselle, Palmers, & Noël, 2004). Some studies even fail to find any evidence of a sensitivity to numerical differences when the perceptual variables, which naturally covary with numerosities, are strictly controlled for (Clearfield & Mix, 1999, 2001Feigenson, Carey, & Spelke, 2002;Mix, 2002;Rousselle et al, 2004).…”
Section: Introductionmentioning
confidence: 99%